2020
DOI: 10.2147/jir.s240421
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association Between Sortilin and Inflammation in Patients with Coronary Heart Disease</p>

Abstract: Purpose: Inflammation is a key contributor to coronary heart disease (CHD). Sortilin is a sorting receptor and has been identified as a critical regulator of inflammatory response. Therefore, our study aimed to determine the link between circulating sortilin levels, proinflammatory cytokine levels, and the occurrence of CHD.Patients and Methods: Our study included 227 CHD patients and 101 matched healthy individuals. Circulating serum levels of sortilin and proinflammatory cytokines, including IL-1β, IL-6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
2
11
0
2
Order By: Relevance
“…Accumulating data indicates that chronic in ammation is controlled by proin ammatory cytokines including IL-1β, IL-6 [20], and TNF-α [21]via immune responses including the recruitment of in ammatory cells to the site of injury and the promotion of adverse vascular smooth muscle cell remodeling play a critical role in atherogenesis. Our study found a reduction of TNF, IL-1, and IL-6 in the CHD group, elevated levels of proin ammatory cytokines were also observed in CHD patients in Han's study [22]. Moreover, an animal model study showed that the transfer of BM de cient in sortlin which is a high-a nity receptor for the proin ammatory cytokines IL-6 and IFN-γ into irradiated atherosclerotic mice reduced atherosclerosis and systemic markers of in ammation [13].…”
Section: Discussionsupporting
confidence: 64%
“…Accumulating data indicates that chronic in ammation is controlled by proin ammatory cytokines including IL-1β, IL-6 [20], and TNF-α [21]via immune responses including the recruitment of in ammatory cells to the site of injury and the promotion of adverse vascular smooth muscle cell remodeling play a critical role in atherogenesis. Our study found a reduction of TNF, IL-1, and IL-6 in the CHD group, elevated levels of proin ammatory cytokines were also observed in CHD patients in Han's study [22]. Moreover, an animal model study showed that the transfer of BM de cient in sortlin which is a high-a nity receptor for the proin ammatory cytokines IL-6 and IFN-γ into irradiated atherosclerotic mice reduced atherosclerosis and systemic markers of in ammation [13].…”
Section: Discussionsupporting
confidence: 64%
“…This rs599839 polymorphism is located on the 1p13.3 chromosomal region near the SORT1 (sortilin-1) gene, which encodes the VPS10P domain-sorting receptors involved in intracellular protein trafficking and the modulation of hepatic very-low-density protein secretion [ 25 , 26 ]. The frequency of the rs599839 polymorphism in the Chinese population has been reported to be higher in CAD patients compared with healthy controls (OR = 8.37, 95% CI: 1.70–41.0); in addition, CAD patients with the AA genotype display higher sortilin levels than those with the GG and GA genotypes (391.25 ± 128.24 ng/L vs. 314.70 ± 64.65 ng/L, p = 0.000) [ 27 ]. Other studies have also shown that the increase in SORT1 expression was negatively correlated with LDLc levels [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Activating proinflammatory factors, such as IL-6 and TNF, can disrupt the endothelial function of blood vessels and accelerate the rupture of plaques, thus accelerating the onset of coronary atherosclerosis. [ 24 ] Therefore, inhibition of inflammatory factor activation can reduce the adverse incidence of cardiovascular events in CHD. VEGFA has been shown to promote microvessel formation and development by binding to vascular endothelial cell receptors to induce their differentiation, proliferation, and migration.…”
Section: Discussionmentioning
confidence: 99%